Efficacy of Connective Tissue with and without Periosteum in Regeneration of Intrabony Defects - Esfahanian, Vahid (J Dent Res Dent Clin Dent Prospects, 2014)
Background and aims. Connective tissue grafts with and without periosteum is used in regenerative treatments of bone and has demonstrated successful outcomes in previous investigations. The aim of present study was to evaluate the effectiveness of connective tissue graft with and without periosteum in regeneration of intrabony defects. Materials and methods. In this single-blind randomized split-mouth clinical trial, 15 pairs of intrabony defects in 15 patients with moderate to advanced periodontitis were treated by periosteal connective tissue graft + ABBM (test group) or non-periosteal connective tissue graft + ABBM (control group). Probing pocket depth, clinical attachment level, free gingival margin position, bone crestal position, crest defect depth and defect depth to stent were measured at baseline and after six months by surgical re-entry. Data was analyzed by Student’s t-test and paired t-tests (α=0.05). Results. Changes in clinical parameters after 6 months in the test and control groups were as follows: mean of PPD reduction: 3.1±0.6 (P<0.0001); 2.5±1.0 mm (P<0.0001), CAL gain: 2.3±0.9 (P<0.0001); 2.2±1.0 mm (P<0.0001), bone fill: 2.2±0.7 mm (P<0.0001); 2.2±0.7 mm (P<0.0001), respectively. No significant differences in the position of free gingival margin were observed during 6 months compared to baseline in both groups. Conclusion. Combinations of periosteal connective tissue graft + ABBM and non-periosteal connective tissue graft + ABBM were similarly effective in treating intrabony defects without any favor for any group. Connective tissue and perio-steum can be equally effective in regeneration of intrabony defects.